A Clathrin-Related Protein, SCD2/RRP1, Participates in Abscisic Acid Signaling in Arabidopsis - Hou, Bingzhu; Shen, Yuanyue (Frontiers in Plant Science, 2020)
Abscisic acid (ABA) plays important roles in many aspects of plant growth and development, and responses to diverse stresses. Although much progress has been made in understanding the molecular mechanisms of ABA homoeostasis and signaling, the mechanism by which plant cells integrate ABA trafficking and signaling to regulate plant developmental processes is poorly understood. In this study, we used Arabidopsis STOMATAL CYTOKINESIS DEFECTIVE 2/RIPENING-REGULATED PROTEIN 1 (SCD2/RRP1) mutants and overexpression plants, in combination with transcriptome and protein-interaction assays, to investigate SCD2/RRP1 involvement in the integration of ABA trafficking and signaling in seed germination and seedling growth. Manipulation of SCD2/RRP1 expression affected ABA sensitivity in seed germination and seedling growth, as well as transcription of several ABA transporter genes and ABA content. RNA-sequencing analysis of Arabidopsis transgenic mutants suggested that SCD2/RRP1 was associated with ABA signaling via a type 2C protein phosphatase (PP2C) protein. The N- and C-terminal regions of SCD2/RRP1 separately interacted with both PYRABACTIN RESISTANCE 1 (PYR1) and ABA INSENSITIVE 1 (ABI1) on the plasma membrane, and SCD2/RRP1 acted genetically upstream of ABI1. Interestingly, ABA inhibited the interaction of SCD2/RRP1 with ABI1, but did not affect the interaction of SCD2/RRP1 with PYR1. These results suggested that in Arabidopsis SCD2/RRP1participates in early seed development and growth potentially through clathrin-mediated endocytosis- and clathrin-coated vesicle-mediated ABA trafficking and signaling. These findings provide insight into the mechanism by which cells regulate plant developmental processes through ABA.